2012
DOI: 10.1002/ejoc.201201020
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Photosensitized Rearrangement and the Lewis‐Acid‐Catalyzed Rearrangement of Spirooxindole Epoxides

Abstract: Spirooxindole epoxides undergo smooth rearrangement either under photosensitization conditions or under Lewis acid catalysis to give different products. The photosensitized rearrangement of spirooxindole epoxides leads to 3‐acyl‐2‐indolones, such as spiro[cycloalkane‐1,3′‐indolin]‐2,2′‐diones, by cleavage of the Cα–O bond followed by alkyl migration. The SnCl4‐catalyzed rearrangement of spirooxindole epoxides gives 4,4‐dialkylquinolin‐2,3‐diones, such as spiro[cycloalkane‐1,4′‐quinolin]‐2′,3′‐diones, by cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Consideration of the mechanisms for conversion of 3 to 7 and 11 to 14 accounted for the novel rearrangements (Figure ). They were triggered by the instability of the highly oxygenated epoxide intermediates that initially form (i.e., I and V ), especially in light of the acidity of the medium . The epoxidation, which follows a “majority rules” model, appears to have been highly diastereoselective because we were only able to detect and isolate one product from each reaction.…”
Section: Figurementioning
confidence: 98%
“…Consideration of the mechanisms for conversion of 3 to 7 and 11 to 14 accounted for the novel rearrangements (Figure ). They were triggered by the instability of the highly oxygenated epoxide intermediates that initially form (i.e., I and V ), especially in light of the acidity of the medium . The epoxidation, which follows a “majority rules” model, appears to have been highly diastereoselective because we were only able to detect and isolate one product from each reaction.…”
Section: Figurementioning
confidence: 98%
“…Gratifyingly, the reaction was complete within 1 minute and gave the desired spiroindolinone 2f in 84% yield (entry 14). Methyl-, methoxy-, chloro-, and fluoro-substituted phenylcyclohexane-1-carboxamides 1g-o also gave very good results under similar conditions (entries [15][16][17][18][19][20][21][22][23]. The reaction of N-3-methylphenylcyclohexane-1-carboxamide 1m produced two regioisomers, 2m (R 2 = Me) and 2m′ (R 4 = Me) in a 2:1 regioisomeric ratio, probably due to the steric hindrance of the methyl group (entry 21).…”
Section: Syn Thesismentioning
confidence: 87%
“…Yield: 97.8 mg (88%); colorless microcrystals (from EtOH/hexane); mp 97-99 °C (Lit. 16 92-94 °C); R f = 0.31 (EtOAc/hexane, 3:7). Hz, 2 H, -CH 2 -CH 2 -CH 3 ), 3.06 (ddd, J = 16.0, 10.5, 5.5 Hz, 1 H, H-CH), 2.59 (dt, J = 13.5, 4.8 Hz, 1 H, H-CH), 2.46-2.38 (m, 1 H, H-CH), 2.26-2.16 (m, 2 H, CH 2 ), 2.12-2.07 (m, 1 H, H-CH), 2.02-1.94 (m, 1 H, H-CH), 1.88-1.84 (m, 1 H, H-CH), 1.73-1.69 (m, 2 H, -CH 2 -CH 2 -CH 3 ), 0.94 (t, J = 7.5 Hz, 3 H, -CH 2 -CH 2 -CH 3 ).…”
Section: ′-Methylspiro[cyclohexane-13′-indoline]-22′-dione (2a) 11amentioning
confidence: 99%
“…While dehydration of 5a,b quantitatively gave 4a,b (vide supra), the treatment of 3a,b under the same conditions resulted retroaldol products 6a,b and 2a (Scheme 3). Since it has been reported that oxindole epoxides were rearranged to quinoline-2,3-dions 8 by treatment with SnCl 4 , 8 we investigated the Lewis acid catalyzed rearrangement of 3 to 8. In consequence, we found that 3a,c,d were rearranged to 8a,c,d and quinoline-2,4-diones 9a,c,d, respectively, by treatment with BF 3 $Et 2 O and HC(OMe) 3 in CH 2 Cl 2 (Scheme 4).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%